A Process Model of Individual Career Decision Making - Mihal, William L.; Sorce, Patricia A.; Comte, Thomas E. (Academy of Management Review, 1984)
A theoretical process model of career decision making is presented. The model draws on research in career theory as well as other areas of decision making. The complex interaction of roles, role expectations, search, and evaluation procedures with the environment is reviewed and integrated in the model. The model and its propositions provide a theoretical framework by which future research may be guided.